Application of laser ablation inductively coupled plasma mass spectrometry mapping technique in environmental samples - Chen, Jie-Mu; 陳玠穆 (2010)
生醫工程與環境科學系 碩士 國立清華大學 We use laser ablation inductively coupled mass spectrometry (LA-ICP-MS) to establish mapping technique for the analysis of elements in environmental and biological samples, which provides high sample throughput, high sensitivity, accuracy and precision of the analytical data for trace and ultra-trace multi-element analysis of solid samples. In this study, a laser beam at a fixed speed (line scan mode) moving along the sample has been used in the LA-ICP-MS mapping technique. MATLAB is utilized to process data, to produce two- or three-dimensional image and to integrate counts for quantitative or qualitative analysis of samples. In addition, a comparison of the proposed method with the laser beam in a fixed position on the sample (grid mode) in analyzing standard samples and real samples are also performed. A better linearity of calibration curves established from standard samples is shown in line scan mode, but similar elemental concentrations are observed by both methods. The proposed mapping technique by LA-ICP-MS is successfully applied in aerosol particulate samples and a slice of lung tissues.